Representasi Kehidupan Sosial Ekonomi Pelaku Usaha Mikro Kecil Menengah (UMKM) Dikawasan Objek Wisata Percandian Muaro Jambi-Provinsi Jambi - Adi Putra (Universitas Muhammadiyah Sidoarjo, 2019)
UMKM are very important to note because UMKM are a driver of national economic development. The important role of UMKM is the most productive sector at the time of the monetary crisis in Indonesia. The development of UMKM is also the most important element for economic development policies to create jobs, equal income, economic growth, alleviate poverty and increase income for the regional economy. This study aims to determine how the socio-economic conditions of UMKM actors in the Tourism Object area of the Muaro Jambi Temple Complex, with descriptive statistical analysis methods, frequency analysis, factor analysis and influence tests to determine the effect of independent variables and dependent variables. the results of this study find out how the socio-economic conditions of Micro, Small and Medium Enterprises in the area of Tourism Object Muaro Jamb ensemble complex, and obtained models and strategies for business development from social capital owned by the community.